Implementasi Algoritma Naïve Bayes Untuk Memprediksi Kerusakan Sepeda Motor Pada Bengkel Citra Djaya Motor - Leni Epriliani; Mayadi; R. Wisnu Prio Pamungkas (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
This research is about the implementation of the Naïve Bayes Algorithm for Predicting Motorcycle Damage at the Citra Djaya Motor Workshop. This system aims to make it easier for workshop employees to check customer motorcycle damage when they want to do service. That way this system can improve services at the Citra Djaya Motor Workshop. Currently, the process of checking motorcycle damage at the Citra Djaya Motor Workshop is still using the manual method in analyzing motorcycle damage. The algorithm used in this study uses the Naïve Bayes algorithm. Making this system using the programming language PHP and Codeigniter as aframework and MySQL database. The results of this research can be implemented in the form of a web-based system.